Fabrication of a TiO2@porphyrin nanofiber hybrid material: a highly efficient photocatalyst under simulated sunlight irradiation. (3rd February 2017) - Duc La, Duong; Rananaware, Anushri; Nguyen Thi, Hoai Phuong; Jones, Lathe; Bhosale, Sheshanath V
Abstract: The solar spectrum consists of 8% UV radiation, while 45% of solar energy is from visible light. It is therefore desirable to fabricate a hybrid material which is able to harvest energy from a wide range of photons from the sun for applications such as solar cells, photovoltaics, and photocatalysis. In this study we report on the fabrication of a TiO2 @porphyrin hybrid material by surfactant-assisted co-assembly of monomeric porphyrin molecules with TiO2 nanoparticles. The obtained TiO2 @porphyrin composite shows excellent integration of TiO2 particles with diameters of 15–30 nm into aggregated porphyrin nanofibers, which have a width of 70–90 nm and are several µm long. SEM, XPS, XRD, FTIR, UV–Vis and fluorescence spectroscopy were employed to characterize the TiO2 @TCPP hybrid material. This material exhibits efficient photocatalytic performance under simulated sunlight, due to synergistic photocatalytic activities of the porphyrin aggregates in visible light and TiO2 particles in the UV region. A plausible mechanism for photocatalytic degradation is also proposed and discussed.